Digital Transformation in Marriage Administration: Evaluating the Implementation of SIMKAH at KUA Medan Barat - Hawani Jannah, Fithra; Sukiati (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
This study examines the implementation of the Marriage Management Information System (SIMKAH) at KUA Medan Barat, focusing on its effectiveness in modernizing marriage registration and administration. The research identifies key challenges in the system’s application and evaluates the extent to which SIMKAH complies with regulatory frameworks, particularly the Instruction of the Director General of Islamic Community Guidance No. DJ.II/369 of 2013 and KMA RI No. 829 of 2019. A qualitative approach was employed, utilizing case study research at KUA Medan Barat. Data were collected through interviews with KUA officials, document analysis, and direct observation of SIMKAH’s operational processes. The study also examined regulatory documents and technical guidelines to assess the system’s implementation. Findings indicate that while SIMKAH has successfully standardized and digitized marriage registration, several challenges persist. These include discrepancies in bride and groom data, falsification of divorce certificates, canceled marriage registrations due to family conflicts, and technical issues such as network disruptions. To mitigate these issues, KUA Medan Barat has implemented measures such as stricter document verification, requiring couples to correct discrepancies at civil registration offices, and promoting early registration to avoid last-minute complications. This study contributes to the literature by providing a comprehensive evaluation of SIMKAH’s practical implementation at the local level. Unlike previous research that broadly discusses digitalization in marriage registration, this study offers an in-depth analysis of the specific challenges faced by KUA Medan Barat and proposes practical solutions for improving SIMKAH’s efficiency. The findings highlight the need for continuous improvements in digital marriage registration systems, including enhanced data security measures, better infrastructure to prevent technical disruptions, and more extensive public outreach programs. The study also suggests that future research should explore SIMKAH’s implementation in other regions to develop a more generalized framework for optimizing digital marriage administration in Indonesia.